Pendekatan Budaya Islam di Madrasah melalui Pengenalan Ilmuan Muslim al-Khazani dengan Konsep Tekanan Udara pada Pembelajaran Fisika - Tiana Azmi Alawiyah (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
Muslim scientists create a lot of great works in the field of science but the findings of Muslims have not been applied by teachers in science learning in madrasah. One of these Muslim scholars was Al Khazini with his findings of air pressure, preceded the western scientist Blaise Pascal (1588-1651 AD). The purpose of this study to reveal that the work of Muslim scientists can be used as a source of science learning in madrasah to be culturally closer to Islam. The research method used is qualitative method by using historical approach of philosophy of science in Islamic perspective. Data were collected through literature study. The results showed that Al-Khazini is revealed about air pressure earlier than Pascal. These findings can be taught in madrasah through methods of sociologically anthropological demonstrations that close to madrasah culture.